The Pre-Service Early Childhood Education Teacher in Developing Child's Story Book - listyowati, anies (THUFULA, 2022)
This research aims to describe prospective PAUD teacher students' ability to develop their creativity when making storybooks for early childhood. This qualitative descriptive study involved 12 prospective PAUD teacher students taking the Creativity and Talents course in the PAUD PG Study Program at a university in Surabaya. The data was obtained from the results of collecting assignments to make story books, while data analysis was done by assessing the percentage through observing the results of making story books based on indicators of creativity in novel story ideas, making storylines, and arranging words in story narrative sentences as well as illustrating pictures and coloring them. The results of research on the creativity of PAUD teacher candidates show that creativity in developing storybooks is good. This can be seen from the results of the percentage of new ideas (84.09%), storylines (76.87%), language (61.12%), and illustrated pictures (98.17%). Based on these results, it is hoped that future PAUD teacher students will be able to make storybooks for children on the theories and needs that exist in their respective schools and it turns out that they can overcome limitations in illustrating pictures with the help of technology and big data available on the internet.